Positive and negative effects of artificial intelligence on students' outlook. - Shakhnoza Rakhmonova; Tolib Kuldoshevich Botirov; Normurodov Khurshid Tursunmurodovich (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Artificial intelligence is a technology that allows computers to perform tasks that humans do, such as creating texts, analyzing data, and making decisions. The most “trending” topic today is artificial intelligence. The 21st century is the century of technology, and technology is the future. One thing we need to know is that the best example of artificial intelligence to date is that new chatbots like ChatGPT are not “smart”. Artificial intelligence translators are really unique in that they can translate any language in the world in a very short time. You can use them to travel to any part of the world. These electronic translators are expected to develop further in the future. Another bad thing about intelligent programs like ChatGPT is that they don't tell you the truth. If you ask them something, they will give you the best answer they have, but they don't have a concept of truth. If they don't know the answer to the question, they will simply fabricate a lie.